2012
DOI: 10.1021/jo202639g
|View full text |Cite
|
Sign up to set email alerts
|

C2 Hydroxyl Group Governs the Difference in Hydrolysis Rates of Methyl-α-d-glycero-d-guloseptanoside and Methyl-β-d-glycero-d-guloseptanoside

Abstract: A computational investigation into the hydrolysis of two methyl septanosides, methyl-α-D-glycero-D-guloseptanoside and methyl-β-D-glycero-D-guloseptanoside was undertaken. These septanosides were chosen as model compounds for comparison to methyl pyranosides and allowed direct comparison of α versus β hydrolysis rates for a specific septanoside isomer. Results suggest that hydrolysis takes place without proceeding through a transition state, an observation that was suggested in previous computational studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[30,54] The acid hydrolysis of guloseptanosides in methanol was investigated by relaxed potential energy scans (M06-2X/6-311 + G**, with methanol represented by a polarizable continuum model). [36] This study showed that the hydroxyl group on the C(2) atom affects the hydrolysis mechanism because of its proximity to the anomeric carbon atom. The calculations predicted that the reaction should be also affected by the hydrogen-bond interaction of the hydroxyl group with the departing methanol from the a anomer.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…[30,54] The acid hydrolysis of guloseptanosides in methanol was investigated by relaxed potential energy scans (M06-2X/6-311 + G**, with methanol represented by a polarizable continuum model). [36] This study showed that the hydroxyl group on the C(2) atom affects the hydrolysis mechanism because of its proximity to the anomeric carbon atom. The calculations predicted that the reaction should be also affected by the hydrogen-bond interaction of the hydroxyl group with the departing methanol from the a anomer.…”
Section: Introductionmentioning
confidence: 94%
“…[1] Substituents at the glycoside and the reaction solvent exert a decisive influence on the reaction pathway. [36,37] A mechanism involving an acyclic carbocation is often proposed for the hydroly-sis of glycosides confronted with ring strain issues or containing a poor leaving group, [38,39] whereas a mechanism through a cyclic carbocation is often assumed for cellulose. [40][41][42][43] Both acyclic and cyclic carbocations should have a short life time in solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations